The Transformation of the Meaning of Halal Certification from the Perspective of MSME Owners Following the Implementation of the Mandatory Halal Policy in 2026 - Rahmawati Rahmawati (Transpublika Publisher, 2026)
The implementation of the mandatory halal policy in 2026 has brought significant changes to the management practices of Micro, Small, and Medium Enterprises (MSMEs). However, studies examining how MSME owners interpret the meaning of halal certification following the implementation of this policy remain relatively limited. This study aims to explore the transformation of the meaning of halal certification from the perspective of MSME owners after the implementation of the 2026 mandatory halal policy. The research employed a qualitative approach using a transcendental phenomenological design. Data were collected through in depth interviews, field observations, and documentation involving MSME owners who had obtained halal certification. The data were analyzed using phenomenological reduction and thematic analysis. The findings reveal that halal certification is no longer perceived merely as a means of complying with regulatory requirements; rather, it has evolved into a business identity, a mechanism for building consumer trust, a business development strategy, and a factor supporting business sustainability. These findings highlight that halal certification serves a broader function as a strategic asset for enhancing the competitiveness of MSMEs. The novelty of this study lies in its exploration of the lived experiences of MSME owners in constructing the meaning of halal certification through a transcendental phenomenological approach, thereby providing a conceptual contribution to the development of halal certification studies in Indonesia, by explaining how the meaning of halal certification is socially constructed beyond regulatory compliance through the lived experiences of MSME owners.